KEBIJAKAN DAN TATA KELOLA OLAHRAGA: STUDI KASUS PADA KONI PROVINSI ACEH - Juliandi, - (2020)
Sports policy is a forum to ensure that everyone has access to various sports activities, whether organized by membership-based sports clubs or independently. An optimal sports policy will result in a good implementation of governance. Good governance is an effective, honest, fair, transparent and accountable government that government institutions need. The purpose of this study is to determine the policy and governance of sports in the Aceh Province KONI. The method used in this research is descriptive qualitative approach. Furthermore, for data collection using documentation study, observation and semi-structured interviews. The findings show that the policies in KONI Aceh have been able to boost Aceh's achievements and that sports governance in KONI Aceh have not been fully implemented, so there are several indicators that have not been applied. Research on sports policy and governance can be used as a reference for increasing the achievement of the objectives of policy and good governance in realizing a better organization. Keywords: Policy, Sports Governance, KONI Aceh.